2005 European Conference on Power Electronics and Applications 2005
DOI: 10.1109/epe.2005.219658
|View full text |Cite
|
Sign up to set email alerts
|

Polyphased modular direct-drive wind turbine generator

Abstract: The goal of the paper is to study the possibility of increasing the power capability of direct-drive PM wind generators with respect to the established quality criteria: electromagnetic torque and the power trasferred to the grid. The studied solution is a polyphased system with a phase number multiple by 3, i.e. a multi-star system. The influence of the number of stars and their phase shift are investigated. -KeywordsWind generator systems, penranent magnet synchronous motor, multiphase drive LOB 2005 -I2'rc.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…Scheme of the WECS based on the SS-PMG. [113]. Besides, the fault tolerant capability of multi-phase machines is better than traditional three-phase machines.…”
Section: Future Trendsmentioning
confidence: 96%
“…Scheme of the WECS based on the SS-PMG. [113]. Besides, the fault tolerant capability of multi-phase machines is better than traditional three-phase machines.…”
Section: Future Trendsmentioning
confidence: 96%
“…Examples can be found in [12][13][14][15]. It can be shown that all the modelling approaches described in [10][11][12][13] yield exactly the same results as those obtained with the so-called Vector Space Decomposition (VSD) approach, which was introduced in [16].…”
Section: Introductionmentioning
confidence: 79%
“…All the different transformation matrices for multiphase machines rely on the fact that the initial set of equations of a multiphase machine can be rearranged in the form of the equations of (n−1)/2 (for odd; (n/2−1) for even phase numbers) mutually independent subspaces or submachines [11], with the remaining component(s) representing zero sequence. In this manner, control of each of the submachines becomes simple and control of all of them leads to control of the original multiphase machine.…”
Section: Introductionmentioning
confidence: 99%
“…[144] describes an AC drive with multiple independent phase driving units. For wind turbines, such a multiple phase system with nine phases constructed with classical three phase converters was described in [145].…”
Section: Fault Tolerancementioning
confidence: 99%